South Kordofan : A Growth Diagnostic - Klugman, Jeni; Wee, Asbjorn (World Bank, Washington, DC, 2013)
This report attempts to diagnose existing constraints and prospects for growth in people's incomes in South Kordofan. Given the breadth and depth of difficulties facing the state, the focus is on identifying the key areas of reform, or binding constraints, to growth. There is a combination of extremely low social returns, the prevalence of government and market failures, the weak investment climate and the limited access to finance to be the primary constraints. In turn it is suggested that policy reforms directed to improving governance, improving investment climate and pro-poor public investment are priorities. One immediate priority pertains to property rights issues which demands comprehensive land reform and clarification of customary land tenure and land dispute resolution mechanisms. Improving market connectivity, water resource management and farm productivity also emerge as keys to enhancing the investment climate in the rural sector. In urban areas, improved transportation networks and access to finance will increase private and social returns to investment. Efforts are also needed to improve the transparency, predictability and levels of intergovernmental transfers to promote pro-poor investment and developmental outcomes. It is suggested that local revenue efforts can improve as and when local service provision and governance are better established. There is recognition that some initial improvements are already underway, including the roads from Dilling to Kadugli and Kadugli to Kauda, and Kadugli to Dilling and Dilling to Dashol, and the railway. Progress is expected to be visible in 2008.